The Negative Aspects of Ampel Corridor Environment as A Historical Commercial Site - Kusumowidagdo, Astrid; Wardhani, Dyah Kusuma (Humaniora, 2017)
The purpose of this study was to investigate the elements that had negative influences on the creation of the atmosphere and uniqueness of the place. Conducted qualitatively descriptive, the data collection was gathered through a focus group discussion method towards eight people in addition to observation, documentation, interview with experts, and document study. This research has found some various elements that have created negative impacts on the Ampel Corridor, such as the narrow distance between stores, lack of cleanliness, unclear circulation, noisy, the informal parking area, and cross-circulation with the settlement. The other factors also include numerous beggars, visitors, and pedicab.